The continuum relationship of aesthetic and social space in the dhikr performativity of the Sambas Malay in West Kalimantan - Ansari, Isa; Abdullah, Irwan; Yusuf, Mohamad (International Journal of Visual and Performing Arts, 2024)
Studies on performative issues in ritual practices often detach social practices from performative studies, emphasizing aesthetic elements instead. This separation creates a divide between aesthetic and social practices. This study seeks to describe dhikr practices that reinforce performative aspects by examining the continuum between aesthetic and social spaces. It highlights the importance of the reciprocal relationship between these two domains, which ultimately redefines the spaces where aesthetic and social practices are performed. The research employs a methodology centered on observations and interviews with informants, categorized by their use of traditional or contemporary songs in performing dhikr. Data analysis was conducted both on-site and off-site. On-site analysis involved recording local terms and describing them within their cultural context. Additionally, transcription was undertaken to convert sounds, movements, and voices into written form. Off-site analysis included verifying data completeness, classifying data based on research needs, reducing irrelevant data, coding the remaining data, and organizing it into themes before presenting it systematically. The findings reveal three key processes within the continuum. First, the configuration of traditional and contemporary songs illustrates a linear progression that reflects the formation of Sambas Malay culture. Second, the configuration of songs and cultural construction is mediated through both cultural and structural platforms. Third, this continuum extends to the internal experiences of dhikr practitioners, serving as a reflective process of their practices. The study’s results have significant implications for understanding dhikr practices, demonstrating that they are not solely religious in nature. It also opens new avenues for research, particularly exploring the political dimensions of dhikr practices and their relationship to power dynamics within the Sambas Malay community.